Paul Ricoeur: Philosophy, theology and happiness - Verhoef, Anné (Stellenbosch Theological Journal, 2018)
Philosophy and theology have diverse and often opposite understandings of happiness. Both offer unique and valuable insights into happiness, but the concept of happiness of both can be criticised on crucial points. Ricoeur's work on happiness at first was as a philosopher, but he changed his discourse to a more religious register, one that appreciates the optative mood of language. It is within this optative mood that Ricoeur manages to bring philosophy'ss and theology's concepts of happiness into a fertile dialectic. The optative and religious images and metaphors provide for him a more holistic and unified way of thinking about happiness in relation to unhappiness and luck. An attempt to translate this optative understanding back to the indicative or imperative by theology and philosophy is futile, because happiness will then be again fragmented and reduced to descriptions and prescriptions.